A facile method for the production of sn-ag alloy by high energy ball milling - SHARMA, ASHUTOSH; AHN, BYUNGMIN (Archives of Metallurgy and Materials, 2020)
In this study, we have developed Sn-Ag alloy by a simple high energy ball milling technique. We have ball-milled the eutectic mixture of Sn and Ag powders for a period of 45 h. The milled powder for 45 h was characterized for particle size and morphology. Microstructural investigations were carried out by scanning electron microscopy and X-ray diffraction studies. The melting behavior of 45 h milled powder was studied by differential scanning calorimetry. The resultant crystallite size of the Sn(Ag) solid solution was found to be 85 nm. The melting point of the powder was 213.6°C after 45 h of milling showing depression of ≈6°C in melting point as compared to the existing Sn-3.5Ag alloys. It was also reported that the wettability of the Sn-3.5Ag powder was significantly improved with an increase in milling time up to 45 h due to the nanocrystalline structure of the milled powder.
Keywords: Eutectic mixture; High-energy ball milling; Melting behavior; Microstructural investigation; Nano-crystalline structures; Particle size and morphologies; Sn-3.5 Ag alloys; X-ray diffraction studies; Ball milling; Electronics; Microstructure; Pb-free; Solder